2010
DOI: 10.3390/toxins2122890
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Neurotoxin for Pain Management: Insights from Animal Models

Abstract: The action of botulinum neurotoxins (BoNTs) at the neuromuscular junction has been extensively investigated and knowledge gained in this field laid the foundation for the use of BoNTs in human pathologies characterized by excessive muscle contractions. Although much more is known about the action of BoNTs on the peripheral system, growing evidence has demonstrated several effects also at the central level. Pain conditions, with special regard to neuropathic and intractable pain, are some of the pathological st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 124 publications
(167 reference statements)
1
60
0
Order By: Relevance
“…Later, its efficacy in reducing mechanical allodynia was reported in sciatic nerve constriction-injury-evoked neuropathy (Luvisetto et al, 2007;Marinelli et al, 2010;Mika et al, 2011). It was observed that BoNT/A accelerates the functional recovery of the injured sciatic nerve in a model of sciatic constriction injury-induced peripheral neuropathy, measured using sciatic static index and regeneration-associated markers (Marinelli et al, 2010;Mika et al, 2011;Pavone and Luvisetto 2010). In addition, BoNT/A prevented the sciatic nerve injury-induced upregulation of pronociceptive opioid neuropeptides and SNAP-25 in the sensory ganglia, and markers of glial activation in the spinal cord (Mika et al, 2011;Vacca et al, 2013).…”
Section: Neuropathic Painmentioning
confidence: 99%
“…Later, its efficacy in reducing mechanical allodynia was reported in sciatic nerve constriction-injury-evoked neuropathy (Luvisetto et al, 2007;Marinelli et al, 2010;Mika et al, 2011). It was observed that BoNT/A accelerates the functional recovery of the injured sciatic nerve in a model of sciatic constriction injury-induced peripheral neuropathy, measured using sciatic static index and regeneration-associated markers (Marinelli et al, 2010;Mika et al, 2011;Pavone and Luvisetto 2010). In addition, BoNT/A prevented the sciatic nerve injury-induced upregulation of pronociceptive opioid neuropeptides and SNAP-25 in the sensory ganglia, and markers of glial activation in the spinal cord (Mika et al, 2011;Vacca et al, 2013).…”
Section: Neuropathic Painmentioning
confidence: 99%
“…Apart from its effect on neuromuscular junction, recent preclinical and clinical studies reported the efficacy of BTX-A in reduction of allodynia and hyperalgesia in pain of different origins (Jabbari and Machado 2011;Pavone and Luvisetto, 2010). Moreover, BTX-A was recently registered for treatment of chronic migraine (Dodick et al, 2010) and several controlled clinical studies in other painful conditions are in progress (Jabbari and Machado, 2011;Singh, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to different types of somatic pain (reviewed by Pavone andLuvisetto, 2010, Matak and) the information related to the beneficial action of BTX-A on pain arising from the viscera is mostly limited to the pelvic region. It was found that local BTX-A injections efficiently decrease pain in patients suffering from bladder pain syndrome/ interstitial cystitis, prostatitis and pelvic-floor muscle disorder (Abbott et al, 2006., Chung et al, 2012, El-Khawand et al, 2013, Gottsch et al, 2011, Kuo, 2013, Pinto et al, 2013, Smith et al, 2004, Zermann et al, 2000.…”
Section: Discussionmentioning
confidence: 99%
“…application, BTX-A failed to affect pain induced by acetic acid, thus indicating that BTX-A's antinociceptive action is predominantly of spinal origin. Since studies on different models of somatic pain demonstrated the antinociceptive effect of BTX-A after peripheral, subcutaneous application (reviewed by Pavone andLuvisetto, 2010, Matak and), here we investigated the effect of i.p. applied BTX-A.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation